2000
DOI: 10.1152/ajpheart.2000.279.3.h1392
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial revascularization aggravates myocardial ischemia around the channels in the immediate phase

Abstract: We examined whether transmyocardial revascularization (TMR) relieves myocardial ischemia by increasing regional perfusion via the transmural channels in acute canine experiments. Regional blood flow during transient coronary ligation (2 min) was compared before and 30 min after TMR, and at the third transient ischemia the mid-left ventricle (LV) was cut and immediately frozen along the short axis for the analysis of NADH fluorescence in the regions around the TMR channels. In low-resolution analysis (2-4 g tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We, and others, have demonstrated that with acute sustained myocardial ischemia due to coronary artery ligation, TMR channels do not protect the myocardium against infarction. [6] More recently, [16] investigators compared regional flow during coronary ligation in canine hearts before and half an hour after TMR. This indicates lack of meaningful oxygenated blood flow through the TMR channels.…”
Section: Does Tmr Mimic Physiology Of Blood Flow In Reptile Hearts?mentioning
confidence: 99%
“…We, and others, have demonstrated that with acute sustained myocardial ischemia due to coronary artery ligation, TMR channels do not protect the myocardium against infarction. [6] More recently, [16] investigators compared regional flow during coronary ligation in canine hearts before and half an hour after TMR. This indicates lack of meaningful oxygenated blood flow through the TMR channels.…”
Section: Does Tmr Mimic Physiology Of Blood Flow In Reptile Hearts?mentioning
confidence: 99%